Future Drivers of Leisure Time Physical Activity in Iran - Ziaee Ali; Aghaei Najaf; Saffari Marjan; Zenouz Reza Yousefi; van Hilvoorde Ivo (Sciendo, 2020)
Physical activity can contribute to societal health and prevent antisocial behaviors. This study explored the driving forces facilitating these goals in Iran's socio-cultural context. Through a literature review, investigation of available political documents, interviews with experts and consensus of the research team, seventy-three driving forces were explored from different domains and then categorised via the STEEPV framework. This framework considers drivers from Social, Technological, Environmental, Economic, Political, and Value/Cultural dimensions. The "sport/sport sciences" domain was also considered as an additional domain. In the next step, a questionnaire with an answer scale of 1 to 7 was distributed among experts. The fuzzy Delphi method was used to analyse the collected data. Results showed eighteen drivers from five domains (social, environmental, economic, technological and sport/sports sciences) dramatically influenced leisure time physical activity (LTPA) in Iran. "Physical activity opportunities for vulnerable groups" was identified as the most important driver for participation in LTPA. Results suggest the need for a multidimensional and thorough consideration by organisations, leisure managers and policymakers to discover methods to promote health-related physical activities in the future.